2019
DOI: 10.1155/2019/5329121
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Performance of the Spot Vision Photo Screener before and after Induction of Cycloplegia in Children

Abstract: Aim. To compare the clinical performance of the Spot Vision Screener used to detect amblyopia risk factors (ARFs) in children before and after induction of cycloplegia; the children were referred because they met the screening criteria of the American Association for Pediatric Ophthalmology and Strabismus (AAPOS). Methods. The Spot Vision Screener and a standard autorefractometer were used to examine 200 eyes of 100 children aged 3–10 years, before and after cycloplegia induction, in terms of ARFs. Sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…Yakar noted that sensitivity and negative predictive value increased with cycloplegia. Therefore, he concluded that measurement using cycloplegia may be useful in selected cases [8]. In the present study, despite a slight difference in sensitivity, there was no increase in negative predictive value.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Yakar noted that sensitivity and negative predictive value increased with cycloplegia. Therefore, he concluded that measurement using cycloplegia may be useful in selected cases [8]. In the present study, despite a slight difference in sensitivity, there was no increase in negative predictive value.…”
Section: Discussioncontrasting
confidence: 42%
“…Although SVS is designed to work without cycloplegia, studies have also compared SVS with autorefractometer and/or retinoscopy and with and without cycloplegia [8]. Yakar noted that sensitivity and negative predictive value increased with cycloplegia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9] Compared with cycloplegic refraction, the results from the Spot Vision photoscreener have shown an overall overestimation of myopia, with a range of −0.17 to −0.49 diopters (D) in children aged 3 to 10 years. 4,[9][10][11] The school was informed of the screening date at least 1 week in advance. If applicable, students were required to remove contact lenses for the examination.…”
Section: Refraction Screeningmentioning
confidence: 99%
“…In the article titled “Clinical Performance of the Spot Vision Photo Screener before and after Induction of Cycloplegia in Children” [1], the spot measurement range in the Introduction was incorrect. The authors cited this range from the article available at https://tvst.arvojournals.org/article.aspx?articleid=2683874; however, in the spot user manual, the measurement range is written as “measuring range is ±7.50 diopters (D) for spherical errors and ±3.00 D for cylindrical errors.” Therefore, “measuring range is ±7.50 diopters (D) for spherical errors and ±3.50 D for cylindrical errors” should be corrected to “measuring range is ±7.50 diopters (D) for spherical errors and ±3.00 D for cylindrical errors.”…”
mentioning
confidence: 99%